Model Alokasi Stasiun Inspeksi dengan Mempertimbangkan Work in Process dan Produk Rework dan Scrap - Yuri Delano Regent Montororing (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
In providing high quality products requires a quality control planning so that the output can be good. Quality control in the production line is based on an inspection by a qualified acceptance of the product. This quality control method is done by flexibly placing the quality control station to separate products in the form of rework to be reworked and scrap to be discarded. Research discussing the quality control station allocation taking into account the inventory of work in process and product rework and scrap not exist, therefore the researcher intends to do so. The development of this model is done by developing the objective function to minimize the total cost of production. Total expenses consist of process cost, inspection cost, waiting cost, quality control station installation costs, rework cost and scrap costs. The goal is to find a configuration allocation quality control stations in the production line at minimum cost. From the results obtained inspection station allocation model that is able to minimize the cost of the assembly and the flexibly to changes in demand parameters, costs, probability of conforming and nonconforming proportions.